(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Eosinophilic Esophagitis (EE) Is Manifested by Infiltration of The Esophageal Mucosa by Eosinophils and Culminates In Clinical Features That May Be Difficult To Distinguish From Those Of Gastroesophageal Reflux Disease (GERD). Objectives: To Assess the Frequency of Eosinophillic Esophagitis Among Patients Undergoing Upper Gastroesophagoscopy for Symptoms of Gerd. Study Design: Cross-Sectional Survey Subjects and Methods: Duration of the study was six months (05-11-2012 to 04-05-2013)in gastroenterology department, medical unit 1, general hospital, lahore. A total of 125 cases were enrolled. All the patients who met the inclusion criteria underwent gastroesophagoscopy. And four biopsies, each from upper, middle and lower esophagus were taken. The biopsy specimen was preserved in 10% formalin and sent for histopathology by a single histopathologist to detect the presence of EE Results: Mean age of the patients was 31.02±5.16 years. Out of 125 patients, 80 patients (64.0%) were male while 45 patients (36.0%) were female. Distribution by symptoms showed 90 patients (72.0%) of heartburn, 60 patients (48.0%) of regurgitation and 44 patients of dysphagia (35.2%). Distribution by oesophagoscopic findings were as follows: normal 78 (62.4%), mucosal furrows 3 (2.4%), exudates 18 (14.4%), lumen narrowing 25 (20.0%), and osophageal rings 5 (4.0%). Mild inflammation was present in 77 patients (61.6%), 41 patients (32.8%) were found to have moderate inflammation and 7 patients (5.6%)were having severe inflammation. Eosinophilic esophagitis was found in 10 patients (8.0%). Conclusion: In The Studied Population Sample Of 125 Patients , 8% Have Been Found To Suffer From Eosinophilic Esophagitis , Hence It Is Narrated That Eosinophilic Esophagitis Should Be Considered In Differential Diagnosis Of Gerd And Mucosal Biopsies Are Warranted For Confirmation.